Bibliometric Analysis of The Scientific Literature on Human Papillomavirus Vaccine Clinical Trials: Analysis of PubMed Database - Sushmitha Mohana Murali; Karpagam Senthamarai Kannan; Merrylda Claribel. S (National Journal of Community Medicine, 2023)
Background: Cervical cancer is the 4th most common cancer in the world caused by human papillomavirus (HPV). A preventive measure for cervical cancer is immunization with the HPV vaccine. Hence globally many clinical trials on HPV vaccines are being performed to prevent HPV infection. This bibliometric analysis is done to determine the trend of clinical trials on HPV vaccines worldwide over the years. Methodology: The articles on HPV vaccine clinical trials were extracted from the PubMed database (Mar 1999 – Sept 2022) and the bibliometric data analysis was done using Microsoft Excel. Result: We extracted 308 articles from the PubMed database and obtained 296 clinical trial articles after removing the non-relevant ones. The majority of the papers were published by institutions in the United States of America (USA) among 39 countries (n=112, 37.8%). Most publications were done by the National Cancer Institute of the USA among 188 institutions worldwide (n=19, 6.4%). The majority of articles were published by more than five authors. Lehtinen M from the Department of Infections and Cancer, German Cancer Research Center has done the most number of publications (n=7). More publications were from the Vaccine journal (n=38). The first three highly cited articles had more than 2000 citations. The years 2015 and 2019 had the highest number of publications (n=25). Conclusion: We can observe a gradual increase in clinical research on the HPV vaccine over the years that accounts for the reduction in cervical cancer cases.